BLADDER EXTROPHY TREATMENT WITH PUBIC DIASTASIS CORRECTION IN AN ADOLESCENT. CLINICAL CASE - O.A. Malakhov; S.P. Yatsik; S.M. Sharkov; S.E. Trankovskiy; B.K. Shamov ("Paediatrician" Publishers LLC, 2011)
Clinical case of bladder extrophy in an 11-years old girl. The presentation covers main pathogenic mechanisms of the disease, diagnostic algorithm and treatment approaches. Key words: Bladder extrophy, children. (Voprosy sovremennoi pediatrii - Current Pediatrics. - 2011; 10 (6): 198-203)